The global potential of log-driven trees for reconstructing forest ecosystems dynamics - Labrecque-Foy, Julie-Pascale; Montoro Girona, Miguel (Frontiers in Ecology and Evolution, 2023)
The composition and structure of modern forest ecosystems result from past and present climate as well as centuries of anthropic and natural disturbances. Concerns related to the integrity and resilience of forests in the context of climate change have led to novel ecosystem-based management methods that require extensive knowledge about the preindustrial state of forests and past disturbance regimes. At the beginning of industrial forest exploitation, waterways were used as the main conduits to transport wood, but the timing and impacts of this log driving remain understudied. Given that an estimated 15% to 50% of log-driven logs sank during their transport, this accumulation of subfossil wood can serve as a proxy tool for reconstructing the dynamics and structure of preindustrial forests and inform modern forest management practices. This review provides a global overview of log driving and highlights the significant value of these submerged logs for disturbance ecology. We demonstrate that log driving was used on most continents, implying that proxy records from subfossil logs may be available from numerous boreal and mountainous regions. Our review is one of the first to illustrate the paleoecological value of log-driving remnants and explain how such a resource provides a valuable tool for understanding past forest ecosystems. Such knowledge is crucial for informing forest management in the face of climate change.